Application of an index of biotic integrity (IBI)to fish assemblage of the tropical Hooghlyestuary - Das, Manas KR; Samanta, Srikanta (Indian Journal of Fisheries, 2011)
The index of biotic integrity (IBI) was applied in 117 km stretch of the freshwater zone of Hooghly estuary in India and the effect of anthropogenic stresson fish assemblage integrity was evaluated. Seven new metrics viz., nativespecies richness, native family richness, benthic species richness, water col-umn species richness, % non-native individuals, % tolerant individuals and %herbivorous individuals were added retaining five original metrics. The numberof native species and families, number of water column species, number ofbenthic species, number of intolerant species and percent individual as herbiv-ores decreased significantly (P< 0.01) whereas the percentage of tolerant spe-cies, percent individual as omnivores and percent individual as carnivores in-creased significantly (P<0.01) in the anthropogenically stressed sites. The in-dex of biotic integrity (IBI) is significantly lower at the stressed sites down-stream. Based on the modification of IBI only 3 or 50% of the sample sitessupported fishery in acceptable condition.